ELIT - Maman A. Djauhari (Jurnal Sosioteknologi, 2011)
Some people are used to saying something without understanding the meanings of a word or term. The term of "politik" is an example. People often read or hear or pronounce the word. However, how many of them are aware of its meaning? As a primitive term, such a world is in the scientific realm. Therefore, this article is designed to reflect and constantly invites us back to basics before we involve ourselves in the play that will be a public watch of the world. Keywords: term, meaning, back to basics